(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The religious event city differs from other cities, and this is due to the nature of its emergence, formation, growth, and event that it contains, and it is necessary to know whether the city is a religious event city or whether a religious event is a city event, and its effect on the city’s emergence and composition and the morphological stages it went through in, the religious event acquires a moral characteristic and a distinctive identity for the city in which it is held and gives it great economic potentials that can be exploited in the development of the city. An event that must be available and applied to a model from the cities of the religious event, which is the holy city of Karbala, and the research reached a number of conclusions, the most prominent of which is that the city had arisen, formed and grown on the impact of the religious event that precedes it in existence and occurrence so that the result is a city of a religious event, while the research recommended the need to adopt eventual indicators Which the research has reached in the validity of launching the name of the city of religious event or not.